Die Heimat der Anderen - Feneberg, Valentin (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
Asylum procedures are full of knowledge gaps. Information from distant countries is difficult to obtain, and asylum decisions are risk assessments about an uncertain future. This book traces the journey of country of origin information, from its judicial investigation to its application in decisions. Drawing on over 40 interviews at administrative courts and an analysis of case law on Syrian draft evaders and on the humanitarian crisis in Afghanistan, it illustrates how judges manage both a lack of evidence and an information overload, and how they arrive at different assessments of the same situation based on the same country of origin information, leading to inconsistent decision-making.